A study on prevalence of text neck syndrome among under-graduate students of a medical college in Puducherry - Kamaraj, Nirupama; Rajasekar, Vedapriya Dande; Rangasamy, Surendar (International Journal Of Community Medicine And Public Health, 2022)
Background: Text neck syndrome denotes the repetitive stress injury due to prolonged usage of electronic gadgets. If the condition is left untreated, could lead to serious permanent damage to nerves and spine. Due to COVID-19 pandemic, the dependence to the electronic gadgets has increased as the academic sessions were conducted via virtual modes. These electronic gadgets were increasingly used for personal or recreational purposes particularly by the college students and this might result in neck pain, shoulder pain and discomfort. The objective of the current study is to determine the prevalence of text neck syndrome using neck disability index (NDI) among the under-graduate medical student and to find out the association between the duration of electronic gadget usage and text neck syndrome among the study population. Methods: A self-administered validated questionnaire (NDI) was used to evaluate the neck pain related disability. Google forms were sent to undergraduate students and 354 responded students were included in our study. Percentage and Chi-square values were analysed. Results: Prevalence of text neck syndrome was 16.7%. Significant association was found between gender, MBBS academic year and duration of electronic gadget usage with significant p values 0.030, 0.001 respectively. Duration of electronic gadget usage and text neck syndrome was associated statistically with significant p value 0.038. Conclusions: We conclude that there is significant disability associated with the duration of electronic gadget usage. We found that, the intensity of the neck pain increases with the duration of electronic gadget usage.